Analysis of the Effect of Work Ethic and Assistance on Mustahik Welfare in the Productive Zakat Program at Bengkulu Province Baznas - Novaldi Arya Pratama (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Economic development aims to improve the standard of living and welfare of its community. The welfare of mustahik is when an individual or group of zakat recipients (mustahik) can achieve a standard of living better than before. This research aims to determine whether work ethic influences the welfare of mustahik, to find out whether mentorship impacts the welfare of mustahik, to analyze how work ethic and mentorship together influence the welfare of mustahik in productive zakat programs, to identify the most dominant factors affecting the welfare of mustahik in productive zakat programs, and to understand the extent of the influence of work ethic and mentorship on the welfare of mustahik in productive zakat programs. This research employs a quantitative research method, utilizing the Partial Least Square (PLS) technique, specifically Outer Loading Test and Inner Loading Test. The sample in this study consisted of 30 beneficiaries, and the data collection method used a questionnaire. The results of this study found that: First, work ethic has a direct impact on the well-being of beneficiaries. Second, mentoring does not have an impact on the well-being of beneficiaries. Third, work ethic (X1) and mentoring (X2) do not influence the well-being of beneficiaries (Y). Fourth, business mentoring does not have a significant impact on the well-being of beneficiaries, but work ethic does provide a significant impact. Fifth, a high work ethic is an important component in improving the well-being of beneficiaries. However, some types of mentoring do not have a significant impact on the well-being of beneficiaries. The estimated influence of work ethic is around 35%, while for mentoring it is < 5%, and the remaining 60% is influenced by variables outside the study